Knowledge representation for health care : AIME 2015 International Joint Workshop, KR4HC/ProHealth 2015, Pavia, Italy, June 20, 2015 : revised selected papers /: AIME 2015 International Joint Workshop, KR4HC/ProHealth 2015, Pavia, Italy, June 20, 2015 : revised selected papers. (2015) - Unknown
No abstract available